Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph19010061
|View full text |Cite
|
Sign up to set email alerts
|

Novaluron Has Detrimental Effects on Sperm Functions

Abstract: Although novaluron is an insect growth regulator with a low mammalian acute toxicity and a low risk to the environment and nontarget organisms, toxic effects of novaluron have been reported. However, no studies have yet evaluated the effect of novaluron on reproduction. Therefore, we examined the effects of novaluron on sperm functions. The spermatozoa of ICR mice were incubated with various concentrations of novaluron to induce capacitation. Then, sperm motion parameters and capacitation status were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
8
2
Order By: Relevance
“…In the present study, we used the dual staining method (combined Hoechst 33258/chlortetracycline fluorescence assessment) to evaluate the capacitation status [22] . The samples were centrifuged at 100 × g for 2.5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we used the dual staining method (combined Hoechst 33258/chlortetracycline fluorescence assessment) to evaluate the capacitation status [22] . The samples were centrifuged at 100 × g for 2.5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, capacitation status was observed using an OLYMPUS BX43 (Olympus, Tokyo, Japan) with fluorescence illumination, using ultraviolet BP340–380/LP425 and BP450–490/LP515 excitation/emission filters for H33258 and chlortetracycline fluorescence, respectively. At least 400 spermatozoa per slide were sorted into four patterns according to the capacitation status: dead (D pattern, blue fluorescence spread evenly on the sperm head), live non-capacitated (F pattern, bright green fluorescence spread evenly on the sperm head), live capacitated (B pattern, bright green fluorescence spread over the acrosomal region and a dark post-acrosomal region), and live acrosome reacted (AR pattern, no fluorescence over the sperm head or bright green fluorescence only in the post acrosomal region) [22] .…”
Section: Methodsmentioning
confidence: 99%
“…4, December 2022 288 factor determining the quality of sperm and have a key role in fertilization. Therefore, analysis of sperm motion parameters and capacitation status are basic approaches in various studies related to reproduction based on capacitation Hwang et al, 2021). Additionally, it has been reported that the sperm motility is change based on incubation time (Alavi and Cosson, 2005;You et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The capacitation status of spermatozoa was measured by the dual staining method [combined chlortetracycline (CTC) fluorescence/Hoechst 33258 (H33258) evaluation] as described previously [ 22 ]. After the staining, at least 400 spermatozoa were classified into four patterns according to their capacitation status: dead (D pattern, blue fluorescence on the sperm head), live non-capacitated (F pattern, bright green fluorescence spread evenly on the sperm head), live capacitated (B pattern, bright green fluorescence in acrosomal region), or acrosome-reacted (AR pattern, no fluorescence on the sperm head or bright green fluorescence only in the post acrosomal region).…”
Section: Methodsmentioning
confidence: 99%